Le corps du voyageur à l’épreuve de la Sibérie (xviie-xxe siècle) - Alain Guyot (Viatica)
The article compares a vast period of different depictions of the lived experiences of travellers in Siberia (17th - 20th centuries). Although their initial intentions were similar, the position of writers regarding their experiences radically differs depending on the period. In fact, 17th-century travel literature recounts the arduous conditions of journeying without describing its toll on the body. Descriptions of the physical effects on the body do not truly appear in texts until the 18th century and during the 19th century, probably linked to a new concern for comfort. From then on, rendering the physical and mental effort had an important place in travel discourse.